Imaging in Ocular Trauma: Optimizing the Use of Ultrasound and Computerised Tomography - M Imran Hameed Daula, Sadaf Imran, Saima Amin (Pakistan Journal of Ophthalmology, 2011)
Purpose: This study was conducted to identify the role of ultrasound (US) and computerized tomography (CT) scan in diagnosis of common ocular traumatic lesion. Material and Methods: A cross sectional observational study was conducted over one year period simultaneously at the Jinnah Postgraduate Medical Center (JPMC), Karachi and the PNS SHIFA hospital, Karachi. Fifty patients with traumatic ocular injuries who were referred by the ophthalmologist for radiological evaluation were included in the study. Data regarding five common traumatic lesions namely intraocular foreign body, vitreous hemorrhage, lens dislocation, retinal detachment and choroidal detachment was analyzed. Results: The age of subjects included in this study ranged from 08 years to 60 years (mean age was 28 ± 1 year). Ultrasound was able to detect the pathologies in 93% of the patients when compared with CT scan. CT scan showed higher accuracy compared to ultrasound in detecting intraocular foreign body (25 patients out of which 24 cases were diagnosed by ultrasound) vitreous hemorrhage (26 patients out of which 22 cases were diagnosed on ultrasound) and lens dislocation (04 patients out of which 02 cases were diagnosed on ultrasound). However ultrasound showed higher accuracy compared to CT scan in detecting retinal detachment (20 patients out of which only 06 cases were diagnosed on CT scan) and choroidal detachment (08 patients while CT was unable to detect any case of choroidal detachment). Conclusion: In the setting of acute ocular trauma CT scan is more accurate in detecting intraocular foreign body, vitreous hemorrhage and lens dislocation whereas ultrasound is superior in diagnosing retinal detachment and choroidal detachment. Combined use of these imaging modalities is recommended in diagnosis and management of post traumatic patients with ocular injuries.